Laboratory evaluation of the effect of waste materials on mechanical properties of asphalt binder and mixture containing combined natural binder and waste polymer - Zhao, Li-Cai; Xu, Liang; Yazdi, Amin (Elsevier Sci Ltd, 2023)
The current study's objective is to examine the characteristics of waste polymer-incorporated natural binder modified binders and combinations. Recycling and making use of waste polymers has gained interest as a possible environmentally and financially responsible bitumen modification method. The goal of the current study was to explore the rheological and mechanical characteristics of mixes and bitumens modified with natural binder that contained various amounts of waste polymer. Original bitumen modified with 5%, 10%, and 15% weight of asphalt binder as well as varied amounts of RPW (3%, 5%, and 7% weight), were all employed as samples of bitumen in the study. Several asphalt binder tests such as conventional tests and rheological ones were performed on binder samples. The results showed that adding waste polymer to the natural binder modified binders enhanced their high-performance temperature, as seen by the decreased penetration and increased softening point values. Results revealed that binders containing 5%, 10% and 15% gilsonite have fatigue life at 2.5% strain about 1.06, 9, and 9.8 times higher than original binder, respectively. Results revealed that addition of 5%, 10% and 15% gilsonite leads to decrease the Jnr value by 36%, 87%, and 96%, respectively. While addition of 3%, 5%, and 7% RPW leads to increase the fatigue life by 1.12, 3.75, 5 times higher than 5% gilsonite modified asphalt. Additionally, the binders treated with waste polymers performed better at low temperatures as seen by their decreased stiffness and enhanced fracture resistance. However, a substantial proportion of waste polymer caused both low and high temperature performance to decline. Overall, this study indicates that waste polymer has the ability to enhance the performance characteristics of naturally occurring binder modified binders, but it is important to carefully evaluate the ideal waste polymer percentage in order to obtain the required performance advantages.
Keywords: Natural binder; Rheological performance; Mechanical properties; Waste polymer